1982
DOI: 10.1038/bjc.1982.264
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus in nasopharyngeal and salivary gland carcinomas of Greenland Eskimoes

Abstract: Summary.-Biopsy specimens from nasopharyngeal carcinomas (NPC) or salivarygland carcinomas (SGC) in Greenland Eskimoes were examined for the presence of Epstein-Barr virus (EBV) DNA and sera from the patients were tested for EBVspecific antibody titres. Six out of 7 NPCs and one from an undifferentiated SGC were positive for EBV DNA. The EBV-specific antibody spectra and titres of the patients with NPC or undifferentiated SGC conformed to the results of earlier studies in other high-incidence areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(63 citation statements)
references
References 32 publications
2
61
0
Order By: Relevance
“…There is now both serological and cellular evidence (Anderson-Anvret et al, 1978;Klein, 1979;Saemundsen et al, 1982) in support of the association reported by Old et al (1966) (Klein, 1979).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…There is now both serological and cellular evidence (Anderson-Anvret et al, 1978;Klein, 1979;Saemundsen et al, 1982) in support of the association reported by Old et al (1966) (Klein, 1979).…”
supporting
confidence: 60%
“…These rates are about twenty times higher than the rates in Denmark (Nielsen & Hart-Hansen, 1982). The EBV genome has been demonstrated in malignant NPC epithelial cells from Greenland Eskimos (Saemundsen et al, 1982). Seroconversion to EBV in Greenland is almost universal by the age of two years (Albeck et al, 1985), indicating early exposure to EBV infection.…”
mentioning
confidence: 99%
“…Certain other carcinomas of tonsillar (Brichacek et al, 1984), supraglottic laryngeal (Brichacek et al, 1983), parotid (Saemundsen et al, 1982) and thymic (Leyvraz et al, 1985) epithelium also appear to show an association with this virus, but in these cases the evidence is less extensive and the consistency of the association has yet to be established.…”
Section: Introductionmentioning
confidence: 98%
“…The majority of the nasopharyngeal carcinomas (NPC) in the Inuit population is the undifferentiated type and infection with Epstein–Barr virus is believed to be one of the most important aetiological factors [3]. Furthermore, studies have found an increased risk of NPC and salivary gland cancer among first degree-relatives and in family clusters supporting the existence of a hereditary component [4].…”
Section: Introductionmentioning
confidence: 99%